Chain of iron - Clare, Cassandra (Clare, Cassandra. Last hours., 2021)
Cordelia Carstairs' romantic dreams must be put on hold when a serial killer begins targeting the Shadowhunters of London, sending the Merry Thieves on the trail of a knife-wielding killer.